Relationship between type and milk production traits in Hariana cattle - Raheja, K L; Dalal, D S (The Indian Journal of Animal Sciences, 2007)
Hariana cows (307), progenies of 15 sires maintained at Government Livestock Farm, Hisar (Haryana), were scored for 13-type traits and also for final type score (FTS) using 50 point (50-99) linear scales with the aim to estimate trends and to determine relationship between sire's breeding value estimates for type and production traits. The annual phenotypic and genetic trends for final type score were negative (-1.08±0.47) and significant (-1.21±0.47) respectively. The annual phenotypic change for milk yield in first 3 lactations was -18.56±7.23 kg, -22.22±7.56 kg and -20.68±9.36 k /year, respectively. The corresponding annual genetic trends for these traits were -72.13±9.46 kg, -96.63±7.88 kg -111.82±15.31 kg, respectively. Sires were evaluated for type and milk yield in first 3 lactations with a model containing stage of lactation and year of calving as fixed effects, age at first calving and age at scoring as covariables and sires as random effect. Fore udder attachment, rear udder width and udder depth had high product moment correlations with final type score (0.61, 0.68 and 0.71) respectively. The corresponding genetic correlations were 0.84, 0.82 and 0.89, respectively. The FTS had high product moment and genetic correlations with milk yield in first 3 lactations. Rear udder width and rear udder height had high positive product moment and genetic correlations with production traits.Estimates of genetic trends indicated that this farm require suitable selection scheme for bringing genetic improvement. It is concluded that udder traits, viz. rear udder depth and rear udder height can beused as a tool for selection of animals to improve both type and production traits.